Clinical outcomes after coarctation surgery in a pediatric population at Heart Center Leipzig – A two-decade experience - Katja Schumacher; Manuela de la Cuesta; Mateo Marin-Cuartas; Muhammed Ikbal Aydin; Sabine Meier; Ingo Dähnert; Michael A. Borger; Martin Kostelka; Marcel Vollroth (Annals of Pediatric Cardiology)
Background: Aortic coarctation (CoA) accounts for 5%–8% of congenital heart defects, and patients’ symptoms can range from neonatal shock to hypertension in adolescence or even adulthood. While surgical repair is the gold standard, catheter-based therapies are increasingly utilized. Despite advancements, complications, and recurrence rates necessitating re-intervention remain concerns. Patients and Methods: We analyzed the postoperative outcomes and long-term intervention rates for pediatric patients undergoing extended end-to-end CoA repair without cardiopulmonary bypass between October 2002 and January 2024 at the Leipzig Heart Center. Data were prospectively collected and retrospectively analyzed. Results: Among 168 patients, the median age at surgery was 11 days (interquartile range [IQR] 6–26). There was no early mortality. Median intensive care unit stay was 4 days (IQR 3-5), and hospital stay was 9 days (IQR 7–12). Early re-intervention during the same hospital stay was required in 3% due to re-coarctation. Median follow-up was 33 months (IQR 7 months-8 years). Long-term survival at 1, 5, 10, and 14 years was 100%, 98.9%, 98.9%, and 98.9%, respectively. Freedom from catheter-based intervention was 74.3%, 70.1%, 67.9%, and 64.8% at the same intervals. Conclusion: Extended end-to-end anastomosis for CoA repair in children yields excellent survival and acceptable long-term outcomes, though re-intervention remains a consideration.